1994
DOI: 10.1248/bpb.17.345
|View full text |Cite
|
Sign up to set email alerts
|

Stimulatory Effect of .BETA.-Alanyl-L-histidinato Zinc on Alkaline Phosphatase Activity in Bone Tissues from Elderly Rats: Comparison with Zinc Sulfate Action.

Abstract: The capability of beta-alanyl-L-histidinato zinc (AHZ) to increase alkaline phosphatase activity in the femoral diaphysis from elderly rats was investigated. The femoral-diaphyseal tissues were removed from weanling (3-week-old) and elderly (10-month-old) female rats. Bone tissues were cultured in Dulbecco's modified Eagle medium (high glucose, 4.5%) supplemented with antibiotics and bovine serum albumin. Among various other bone-stimulating factors (AHZ; 10(-5) M, zinc sulfate; 10(-4) M, sodium fluoride; 10(-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

1995
1995
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Studies refer to ‘the three-way regulation’ model of bone metabolism, which consists of the imbalance of regulation of the coupling of bone vessels, osteoclasts and osteogenesis, which leads to a decrease in cortical thickness and an increase in cortical porosity ( 45 , 46 ). The histomorphology and cytokines related to bone metabolism in ovariectomized rats confirmed that the oral administration of ZnC (10–100 mg/kg/day) for 6 weeks can significantly increase zinc accumulation, bone protein synthesis and collagen contents in bone, completely block the bone loss of femoral trabecula and prevent the deterioration of cortical bone ( 47 ). Comparatively low doses of ZnC (10 and 30 mg/kg/day) possess the same ameliorating actions ( 48 ).…”
Section: Mechanism and The Potential Effect Of Carnosine Compounds On...mentioning
confidence: 85%
See 1 more Smart Citation
“…Studies refer to ‘the three-way regulation’ model of bone metabolism, which consists of the imbalance of regulation of the coupling of bone vessels, osteoclasts and osteogenesis, which leads to a decrease in cortical thickness and an increase in cortical porosity ( 45 , 46 ). The histomorphology and cytokines related to bone metabolism in ovariectomized rats confirmed that the oral administration of ZnC (10–100 mg/kg/day) for 6 weeks can significantly increase zinc accumulation, bone protein synthesis and collagen contents in bone, completely block the bone loss of femoral trabecula and prevent the deterioration of cortical bone ( 47 ). Comparatively low doses of ZnC (10 and 30 mg/kg/day) possess the same ameliorating actions ( 48 ).…”
Section: Mechanism and The Potential Effect Of Carnosine Compounds On...mentioning
confidence: 85%
“…Other experiments in elderly (10-month-old) female rats found that when the bone tissues were cultured for 24 h in a medium containing ZnC (10 −5 M), 4.5% glucose, 0.25% bovine serum albumin and antibiotics, the activity of ALP in osteoblasts was significantly increased and prolonged, thus lengthening the cell cycle. ZnC could also activate aminoacyl-tRNA synthetase, a key enzyme in the process of bone protein biosynthesis and translation, stimulate bone formation and mineralization and alleviate senile osteoporosis ( 47 , 58 ).…”
Section: Mechanism and The Potential Effect Of Carnosine Compounds On...mentioning
confidence: 99%
“…Polaprezinc administration induces a superior increase in Zn, DNA, calcium contents, and ALP activity compared to the other zinc-based compounds at the same doses [212]. In another study, Kisi S. and Yamaguchi M. show that polaprezinc significantly increased ALP activity in the femoral diaphysis of elderly rats [213].…”
Section: Beneficial Effects Of Carnosine and Its Zinc Complex Polapre...mentioning
confidence: 96%
“…β-Alanyl-histidinato zinc (AHZ) has been shown to have a potent effect on osteogenesis as compared with that of zinc sulfate [47]. Oral administration of AHZ has been shown to have a preventive effect on bone loss, which is caused with aging [48], inflammation [36], and ovariectomy [49].…”
Section: Zinc Suppresses Osteoclastic Bone Resorptionmentioning
confidence: 99%